2023
DOI: 10.1101/2023.05.08.539795
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Crucial neuroprotective roles of the metabolite BH4 in dopaminergic neurons

Abstract: Dopa-responsive dystonia (DRD) and Parkinson's disease (PD) are movement disorders caused by the dysfunction of nigrostriatal dopaminergic neurons. Identifying druggable pathways and biomarkers for guiding therapies is crucial due to the debilitating nature of these disorders. Recent genetic studies have identified variants of GTP cyclohydrolase-1 (GCH1), the rate-limiting enzyme in tetrahydrobiopterin (BH4) synthesis, as causative for these movement disorders. Here, we show that genetic and pharmacological in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 146 publications
0
2
0
Order By: Relevance
“…BH4 is an essential co-factor for enzymes involved in various cellular processes, for instance nitric oxide production, phenylalanine metabolism, and neurotransmitter biosynthesis, including dopamine synthesis (Werner et al, 2011). Cronin and colleagues observed that BH4 enhanced mitochondrial fitness and maintained firing rates of dopaminergic neurons (Cronin et al 2023). In our model, comparable effects were fulfilled by dopamine administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BH4 is an essential co-factor for enzymes involved in various cellular processes, for instance nitric oxide production, phenylalanine metabolism, and neurotransmitter biosynthesis, including dopamine synthesis (Werner et al, 2011). Cronin and colleagues observed that BH4 enhanced mitochondrial fitness and maintained firing rates of dopaminergic neurons (Cronin et al 2023). In our model, comparable effects were fulfilled by dopamine administration.…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, in pathological conditions (represented by PD patient derived hiPSC-neurons with a 3x SNCA mutation) dopamine treatment led to a rescue effect shown by improved respiration, activation of antioxidant pathways (shown by SOD2 levels), and a series of positive effects on metabolites involved in mitochondrial function. In a recent work it has been found that tetrahydrobiopterin (BH4) protected from genetically and chemically induced PD-related stressors in mice and human neurons from PD patients (Cronin et al, 2023). BH4 is an essential co-factor for enzymes involved in various cellular processes, for instance nitric oxide production, phenylalanine metabolism, and neurotransmitter biosynthesis, including dopamine synthesis (Werner et al, 2011).…”
Section: Discussionmentioning
confidence: 99%